2022
DOI: 10.1002/aur.2787
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and change in loneliness and stress during the COVID‐19 pandemic: A longitudinal study of autistic and non‐autistic adults

Abstract: Previous studies have suggested that autistic adults may be negatively affected by the COVID‐19 pandemic and its associated restrictions. In this study, we examined continuity and change in loneliness and stress, and their predictors, in 448 autistic and 70 non‐autistic adults living in the Netherlands. Autistic participants were assessed on three occasions using the de Jong Gierveld Loneliness Scale and Perceived Stress Scale (pre‐lockdown (T0), first lockdown (T1), and second lockdown (T2)); non‐autistic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Unsurprisingly, some of these studies also reported substantial differences within individuals , with some Autistic adults experiencing both positive and negative effects of the stay-at-home orders at different points during the pandemic [ 27 , 44 ••, 46 , 52 ••, 53 ]. This latter finding might provide one explanation for the apparent stability in psychological wellbeing reported by several prospective, quantitative studies [ 47 •, 48 , 49 ]. Another possibility is that such stability is driven more by the consistently deeply unsatisfactory quality of life and poor mental health experienced by many Autistic adults pre-pandemic (see [ 14 ], for review) than the impact of the pandemic itself.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Unsurprisingly, some of these studies also reported substantial differences within individuals , with some Autistic adults experiencing both positive and negative effects of the stay-at-home orders at different points during the pandemic [ 27 , 44 ••, 46 , 52 ••, 53 ]. This latter finding might provide one explanation for the apparent stability in psychological wellbeing reported by several prospective, quantitative studies [ 47 •, 48 , 49 ]. Another possibility is that such stability is driven more by the consistently deeply unsatisfactory quality of life and poor mental health experienced by many Autistic adults pre-pandemic (see [ 14 ], for review) than the impact of the pandemic itself.…”
Section: Resultsmentioning
confidence: 68%
“…Only 10 (31%) studies were prospective, where the wellbeing of Autistic adults was assessed repeatedly over time. These prospective studies revealed mixed experiences, demonstrating either overall stability of psychopathology symptoms, loneliness and stress in Autistic adults during the first months of the pandemic [ 47 •, 48 , 49 ], an overall decrease in psychopathology symptoms [ 44 ••] or an increase in acute psychiatric distress, as evidenced by increased psychiatric emergency admissions of Autistic adults before and during lockdown [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheeren et al. ( 65 ), for example, observed consistent levels of psychological distress among both autistic and non-autistic adults, and a representative study from Austria reported that the number of study participants out of the general population with clinically relevant symptoms remained unchanged from April to September 2020 ( 66 ). Investigating another sample in Austria, Oppenauer et al.…”
Section: Discussionmentioning
confidence: 99%